Gas explosion in closed pipe with and without 90 degree bends - Md. Kasmani, Rafizian (2012)
An experimental study has been carried out to investigate the explosion properties in pipeline with and without 90 degree bends i.e, flame speeds, overpressure and rate of pressure rice.